Artifice and Medium-Specific Art: Poetry Performance and Film - Geneviève Cohen-Cheminet (Sillages Critiques)
This paper presents a digital artefact (trailer and DVD) made out of the film archive of poet Jerome Rothenberg’s performance-conferences given at the Sorbonne and at the ENS-LSH in November 2005. The editing work undertaken with film artist Meryem De Lagarde led to a clearer understanding of issues of remediation, immediacy and hypermediacy, from the oppositional, Modernist legacy of artifice to the contemporary awareness of our collective, compliant fascination with images. Finally, editing raised issues of poetry film as genre, of medium-specific arts and of critical art.